Advancing Molecular Spectroscopy Efficiency with Extensive Parallelism - Jiaqi Li; Rodrigo Fernandez; Bernardo Gutierrez; Jan Pedersen; Yan Zhou (Metrology)
Molecular spectroscopy, with a legacy spanning over a century, has profoundly enriched our understanding of the microscopic world, driving major advancements across science and engineering. Over time, this field has steadily advanced, incorporating innovations such as lasers and digital computers to reach new levels of precision and sensitivity. Over the past decade, the integration of high-speed embedded electronic systems and advanced light sources has ushered molecular spectroscopy into a new era, characterized by extensive parallelism and enhanced sensitivity. This review delves into two pioneering technologies that embody recent advancements in molecular spectroscopy: Chirped-Pulse Fourier Transform Microwave (CP-FTMW) spectroscopy and optical frequency comb (OFC) spectroscopy. We provide an overview of the fundamental principles behind these methods, examine their most impactful applications across diverse fields, and discuss their potential to drive future developments in molecular spectroscopy. By highlighting these technologies, we aim to underscore the transformative impact of integrating high-speed digital electronics and advanced light sources with molecular spectroscopy, enabling extensive parallelism and paving the way for groundbreaking discoveries and innovations in this rapidly evolving field.